Human papilloma viruses - McCance, Dennis J. (Perspectives in medical virology, 2002)
This book describes up-to-date information on the pathogenesis and molecular biology of human papillomaviruses and describes the mechanistic role of the viruses in epithelial cancers. Included in the book are chapters on the epidemiology of human papillomaviruses, the factors that control replication and transcription and the viral proteins, which are involved in modulating the biology of the host cell leading to cancer. Details of the immune response to the viruses and potential vaccine strategies are discussed.